1993
DOI: 10.1111/j.1365-2958.1993.tb01158.x
|View full text |Cite
|
Sign up to set email alerts
|

PilS and PilR, a two‐component transcriptional regulatory system controlling expression of type 4 fimbriae in Pseudomonas aeruginosa

Abstract: Transposon mutagenesis was used to identify genes necessary for the expression of Pseudomonas aeruginosa type 4 fimbriae. In a library of 12,700 mutants, 147 were observed to have lost the spreading colony morphology associated with the presence of functional fimbriae. Of these, 28 had also acquired resistance to the fimbrial-specific bacteriophage PO4. The mutations conferring this phage resistance were found to have occurred at at least six different loci, including the three that had been previously shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
137
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(140 citation statements)
references
References 76 publications
0
137
0
1
Order By: Relevance
“…PilS and PilR belong to the family of two-component transcriptional regulatory systems that have been described in many bacterial species (Hobbs et al, 1993). PilS is a predicted sensory protein that, when stimulated by the appropriate environmental signals, activates PilR through kinase activity; PilR then regulates transcription of pilA (Hobbs et al, 1993). We have shown that the pilR mutant lacks type IV pili, and does not twitch, which may result from lack of pilA expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PilS and PilR belong to the family of two-component transcriptional regulatory systems that have been described in many bacterial species (Hobbs et al, 1993). PilS is a predicted sensory protein that, when stimulated by the appropriate environmental signals, activates PilR through kinase activity; PilR then regulates transcription of pilA (Hobbs et al, 1993). We have shown that the pilR mutant lacks type IV pili, and does not twitch, which may result from lack of pilA expression.…”
Section: Discussionmentioning
confidence: 99%
“…The gene cluster in P. aeruginosa is thought to function in type IV pilus biogenesis and twitching motility (Mattick, 2002;Hobbs et al, 1993). PilS and PilR belong to the family of two-component transcriptional regulatory systems that have been described in many bacterial species (Hobbs et al, 1993). PilS is a predicted sensory protein that, when stimulated by the appropriate environmental signals, activates PilR through kinase activity; PilR then regulates transcription of pilA (Hobbs et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many T4P-expressing species, including M. xanthus, D. nodosus, G. sulfurreducens, Kingella kingae, Xanthomonas axonopodis, and P. aeruginosa, the major pilin subunit is expressed from a 54 -dependent promoter (Fig. 7) (182,197,218,239,418,423). The complex formed by RpoN and RNA polymerase (RNAP) binds such promoters but remains stalled in a closed configuration.…”
Section: Transcriptional Regulationmentioning
confidence: 99%